2004
DOI: 10.7326/0003-4819-140-1-200401060-00007
|View full text |Cite
|
Sign up to set email alerts
|

Differential Time to Positivity: A Useful Method for Diagnosing Catheter-Related Bloodstream Infections

Abstract: Differential time to positivity of 120 minutes or more is highly sensitive and specific for catheter-related bacteremia in patients who have short- and long-term catheters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
137
1
18

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 310 publications
(162 citation statements)
references
References 14 publications
3
137
1
18
Order By: Relevance
“…DTP was defined as the difference in the time it took for a blood culture drawn through the CVC and a culture drawn from a peripheral vein to become positive. Since then, four studies have confirmed the utility of DTP for the diagnosis of CRI in patients with cancer, [11][12][13][14] and one study of adults in a medical surgical ICU did not confirm its utility. 15 Four of these studies [9][10][11]15 used the catheter-tip-culture/ clinical criteria as the criterion standard, two studies used paired quantitative blood cultures, 12,13 and one study 14 used both methods.…”
Section: Related Bloodstream Infection; Hematopoietic Stem Cell Transmentioning
confidence: 99%
“…DTP was defined as the difference in the time it took for a blood culture drawn through the CVC and a culture drawn from a peripheral vein to become positive. Since then, four studies have confirmed the utility of DTP for the diagnosis of CRI in patients with cancer, [11][12][13][14] and one study of adults in a medical surgical ICU did not confirm its utility. 15 Four of these studies [9][10][11]15 used the catheter-tip-culture/ clinical criteria as the criterion standard, two studies used paired quantitative blood cultures, 12,13 and one study 14 used both methods.…”
Section: Related Bloodstream Infection; Hematopoietic Stem Cell Transmentioning
confidence: 99%
“…A análise da DTP baseia-se na diferença de tempo entre hemoculturas positivas de sangue periférico e sangue de cateter coletadas com intervalo máximo de 15 minutos e com volumes iguais (2,3,15,23,24) . Para diferenças ≥ 120 minutos entre o tempo de positividade (TP) de hemocultura central e periférica, interpreta-se como possível ICSRC, lembrando que o microrganismo isolado deve ser o mesmo em ambas as hemoculturas (3,23) . Equipamentos automatizados de hemoculturas fazem leituras dos frascos em intervalos curtos e contínuos de tempo, possibilitando, desse modo, determinar a curva de crescimento do microrganismo e gerando um gráfico de positividade de fácil acompanhamento.…”
unclassified
“…Equipamentos automatizados de hemoculturas fazem leituras dos frascos em intervalos curtos e contínuos de tempo, possibilitando, desse modo, determinar a curva de crescimento do microrganismo e gerando um gráfico de positividade de fácil acompanhamento. Essa técnica, porém, apresenta limitações na fase pré-analítica, que deve ser muito bem padronizada, e também quando o antibiótico é administrado antes da coleta de sangue pelo acesso venoso central (6,23) .…”
unclassified
See 1 more Smart Citation
“…[8][9][10] Recently, it has been shown that CRBIs can be detected by the Gram stain and acridine orange leukocyte cytospin (AOLC) test 11 or the differential-time-to-positivity (DTP) method, without catheter removal. 12,13 The aim of the present prospective study was to assess the validity of the Gram stain-AOLC test for the diagnosis of CRBI in HSCT recipients with nontunnelled CVCs, using the DTP/clinical criteria as the criterion standard to define CRBIs.…”
Section: Introductionmentioning
confidence: 99%